A new species of Troglocharinus Reitter, 1908 (Coleoptera, Leiodidae, Cholevinae, Leptodirini) from southern Catalonia, with a molecular phylogeny of the related species group - Rizzo, V.; Comas, J. (Zootaxa, 2015)
In this paper we describe T. pallisei sp. n., a new representative of the genus Troglocharinus Reitter, 1908 (Coleoptera, Leiodidae, Leptodirini), a strictly subterranean genus restricted to the Eastern Pyrenees and some coastal areas in Catalonia. All known specimens of T. pallisei sp. n. were collected in a cave next to the town of La Riba, in the province of Tarragona (Spain), situated between the distribution areas of the species of the T. orcinus complex and T. espanoli Jeannel, 1930. It can be separated from the other members of the T. orcinus complex by the presence of penicillus in the apex of the parameres of the aedeagus and from T. espanoli by the presence of a mesoventral keel; it also differs from both by its long and erect pubescence. A Bayesian molecular phylogeny including representatives of the main lineages within the genus Troglocharinus, based on ca. 5211 Kb of 5 mitochondrial and 4 nuclear genes, placed T. pallisei sp. n. as sister to T. orcinus Jeannel, 1910, and both sister to T. espanoli, in perfect agreement with their geographic distributions and the inferred geographic expansion of the genus to the south, with an estimated divergence of ca. 1.3 Ma. In agreement with the results of a previous phylogenetic study, the subgenus Antrocharidius Jeannel, 1910 is synonymised with Troglocharinus (syn.n.).